Optimizing online business management in the fashion sector in increasing sales volume - Nurhilalia Nurhilalia; Muhammad Yusuf; Firman Menne; Sitti Mujahida Baharuddin; Lukman Setiawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The business world is a business that has the potential to improve the welfare of business actors. Every business actor certainly wants his sales volume to increase which means his income will also increase, including online business people in the fashion sector. This study aims to determine how to optimize online business management so as to increase income insights that will be used for business development and business expansion so as to minimize unemployment through the employment opportunities needed. The research method used is descriptive quantitative with data collection techniques through observation, interviews, documentation and distributing questionnaires via g-form. The number of respondents was 200 people selected by purposive sampling. The results showed that there are several proven ways to increase sales volume, namely determining the target market, product quality and guarantee, store design, promotion and financial management. Through these strategies, it is known that business people who experience a decline in sales volume can gradually increase their income again.